Tracking past changes in lake-water phosphorus with a 251-lake calibration dataset in British Columbia: tool development and application in a multiproxy assessment of eutrophication and recovery in Osoyoos Lake, a transboundary lake in Western North America - Cumming, Brian F.; Laird, Kathleen R.; Gregory-Eaves, Irene; Simpson, Kyle G.; Sokal, Mike A.; Nordin, Rick; Walker, Ian R. (Frontiers in Ecology and Evolution, 2015)
Recently there has been an active discussion about the potential and challenges of tracking past lake-water trophic state using paleolimnological methods. Herein, we present analyses of the relationship between modern-day diatom assemblages from the surface sediments of 251 fresh-water lakes from British Columbia and contemporary limnological variables. Total phosphorus (TP) was significantly related to the modern distribution of diatom assemblages. The large size of this new calibration dataset resulted in higher abundances and occurrences of many diatom taxa thereby allowing a more accurate quantification of the optima of diatom taxa to TP in comparison to previous smaller calibration datasets. Robust diatom-based TP inference models with a moderate predictive power were developed using weighted-averaging regression and calibration. Information from the calibration dataset was used to interpret changes in the diatom assemblages from the north and south basins of Osoyoos Lake, in conjunction with fossil pigment analyses. Osoyoos Lake is a large salmon-bearing lake that straddles the British Columbia-Washington border and has undergone cultural eutrophication followed by recovery due to substantial mitigation efforts in managing sources of nutrients. Both diatom assemblages and sedimentary pigments indicate that eutrophication began c. 1950 in the north basin and c. 1960 in the southern basin, reaching peak levels of production between 1960 and 1990, after which decreases in sedimentary pigments occurred, as well as decreases in the relative abundance and concentrations of diatom taxa inferred to have high TP optima. Post-1990 changes in the diatom assemblage suggests conditions have become less productive with a shift to taxa more indicative of lower TP optima in concert with measurements of declining TP, two of these diatom taxa, Cyclotella comensis and Cyclotella gordonensis, that were previously rare are now abundant.